2013
DOI: 10.1186/1471-2458-13-378
|View full text |Cite
|
Sign up to set email alerts
|

Preventive home visits and health – experiences among very old people

Abstract: BackgroundAs more people reach older age, there is a growing interest in improving old person’s health, activity, independence and social participation, thereby adding quality to the extended years. Preventive home visits (PHV) programs for old people have received much attention in recent decades. A large body of research shows mixed effects, and argues that a home visit is a complex social process influenced by numerous factors. To evaluate the impact of PHV, as well as making decisions on whether, how, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
72
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(80 citation statements)
references
References 41 publications
4
72
1
3
Order By: Relevance
“…Consistent with our findings, communication skills and building a positive relationship are seen by older people as a vital part of their services 191,193,194 and have been emphasised in other participatory design processes around frailty prevention. 195 Addressing cognitive, social, psychological and home environment dimensions within frailty prevention services have been advocated by stakeholders 170 and physical and occupational therapists.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with our findings, communication skills and building a positive relationship are seen by older people as a vital part of their services 191,193,194 and have been emphasised in other participatory design processes around frailty prevention. 195 Addressing cognitive, social, psychological and home environment dimensions within frailty prevention services have been advocated by stakeholders 170 and physical and occupational therapists.…”
Section: Discussionsupporting
confidence: 89%
“…Building on the evidence base, we were able to identify what a new service should contain and how it could best be delivered, and refine this iteratively in consultation with older people, professionals, commissioners and providers. Although previous qualitative work has canvassed older people's experiences of transitioning to frailty or general health promotion in later life, 180,182,191,192 none to date has focused specifically on older people's views of health promotion in mild frailty. We incorporated a wide range of views from a range of older people with and without mild frailty, carers, community health and social care professionals, policy-makers and commissioners and were able to make practical recommendations on the content of a new service.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the importance of taking an interest in the older person was highlighted in a Swedish qualitative study about experiences of pre‐frail very old people who received preventive home visits to identify unmet needs and provide local service information (Dahlin‐Ivanoff et al, ). Interestingly, that study reported some people thought that such interventions were not for them because they were too ill or felt too old with nothing to anticipate (Behm, Ivanoff, & Zidén, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous qualitative studies of experiences of preventative home visit (health promotion) services for people aged 80+ or with long‐term conditions suggest that they are valued for providing an accessible contact and psychosocial support through good communication skills (Behm, Ivanoff, & Zidén, ; Williams, Smith, Chapman, & Oliver, ). This aligns with our findings, which further suggest that health promotion services are more likely to be acceptable if delivered by a non‐specialist support worker rather than a clinician.…”
Section: Discussionmentioning
confidence: 99%